Development of multiplex-PCR assay for rapid detection of Candida spp. (Medical Journal of Indonesia, 2010)
Aim Candida spp. infection commonly occur in immunocompromised patients. Biochemical assay for identification of Candida spp. is time-consuming and shows many undetermined results. Specific detection for antibody, antigen and metabolites of Candida spp. had low sensitivity and specificity. In this study, we developed a rapid diagnostic method, Multiplex-PCR, to identify Candida spp. Methods Five Candida spp. isolates were cultured, identified with germ tube and API®20 C AUX (BioMerieux®SA) kit. Furthermore, DNA was purified by QIAamp DNA mini (Qiagen®) kit for Multiplex-PCR assay. Results DNA detection limit by Multiplex-PCR assays for C. albicans, C. tropicalis, C. parapsilosis, C. krusei and C. glabrata were 4 pg, 0.98 pg, 0.98 pg, 0.5 pg and 16 pg respectively. This assay was also more sensitive than culture in that Multiplex-PCR could detect 2.6-2.9 x 100 CFU/ml, whereas culture 2.6-2.9 x 102 CFU/ml. Conclusion Multiplex-PCR is much more sensitive than culture and thus, can be recommended as a sensitive andÂ specific assay for identification of Candida spp. (Med J Indones 2010; 19:83-7)